An Ultralong, Highly Oriented Nickel‐Nanowire‐Array Electrode Scaffold for High‐Performance Compressible Pseudocapacitors. Issue 21 (8th April 2016) - Xu, Chao; Li, Ziheng; Yang, Cheng; Zou, Peichao; Xie, Binghe; Lin, Ziyin; Zhang, Zhexu; Li, Baohua; Kang, Feiyu; Wong, Ching‐Ping
Abstract : Ultralong, highly oriented Ni nanowire arrays are used as the electrode scaffold to support metal‐oxide‐ and conductive‐polymer‐based electrode materials with a high mass loading; the as‐obtained asymmetric supercapacitor can be compressed by fourfold and exhibits superior energy and power densities with ultrahigh cycle stability.